"A Good Death"—Sequence (Not Stigma), to an Enigma Called Life: Case Report on End-of-Life Decision Making and Care. (November 2013) - Bhatnagar, Sushma; Joshi, Saurabh
Fear of death and the stigma associated with the terminal events of illness prevents us from dying well. Lack of recognition of palliative care as a speciality, in many countries, leads us to die a pathetic death in ICU rather than dying at home with near and dear ones around. Its time to break the taboo of death and to start talking about this terminal sequence (good death) of good living.